Wall Street : America's dream palace - Fraser, Steve, 1945- (New Haven : Yale University Press, 2008)
Wall Street: no other place on earth is so singularly identified with money and the power of money. And no other American institution has inspired such deep moral, cultural, and political ambivalence. Is the Street a bulwark defending commercial order? Or is it a center of mad ambition? This book recounts the colorful history of America's love-hate relationship with Wall Street. Historian Steve Fraser frames his analysis around the roles of four iconic Wall Street types--the aristocrat, the confidence man, the hero, and the immoralist--all recurring figures who yield surprising insights about how the nation has wrestled, and still wrestles, with fundamental questions of wealth and work, democracy and elitism, greed and salvation.--From publisher description.
The Aristocrat -- The confidence man -- The hero -- The Immoralist.
Series from jacket.
Includes bibliographical references (pages 181-192) and index
Keywords: Capitalists and financiers -- United States -- Biography; Wall Street (New York, N.Y.) -- History